Analysis of Land Use Suitability Towards Detailed Spatial Plan (Case Study: Kuta Selatan District, Badung Regency, Bali) - M. Abdul Basyid; Didiek Setiadi Ulumuddin (Fakultas Teknik, 2023)
South Kuta District is located in the south of Badung Regency, precisely at 8º46'58.7